Choroidal thickness and vascular density in macular telangiectasia type 2 using enface swept-source optical coherence tomography. Issue 11 (2nd January 2019) - Wang, Jay C; Laíns, Inês; Oellers, Patrick; Kim, Ivana K; Miller, Joan W; Miller, John B
Abstract : Purpose: To investigate the choroidal thickness (CT) and choroidal vascular densities (CVD) of patients with macular telangiectasia type 2 (MacTel2) and their association with other multimodal imaging features, using swept-source optical coherence tomography (SS-OCT). Methods: Prospective, cross-sectional study. Consecutive patients with MacTel2 along with controls without any macular disease were included. Fundus photography, confocal blue reflectance, near-infrared reflectance, autofluorescence, fluorescein angiography, spectral domain OCT and SS-OCT were performed. Images were independently analysed by two graders, and CVD was calculated from binarised en face SS-OCT images. CT was obtained from the SS-OCT platform via built-in automated segmentation. Multilevel mixed-effects models were used for statistical analysis. Results: Thirty-nine eyes of 20 patients with MacTel2 and 29 eyes of 15 control patients were included. Average CT and perifoveal temporal CT did not differ significantly between eyes with MacTel2 and control eyes (p≥0.350), when accounting for confounding factors. Overall and temporal CVD also did not significantly differ between the two groups (p≥0.490). Conclusion: CT and CVD did not significantly differ between MacTel2 and control eyes in this study using SS-OCT. Even though MacTel2 may include abnormalities involving the choroid, these are likely minor in comparison to the predominant retinal changes.